Effect of Octreotide on Hepatic Steatosis in Diet-Induced Obesity in Rats - Li, Mao (PLoS One, 2016)
BACKGROUND: Non-alcoholic fatty liver disease (NAFLD) caused by liver lipid dysregulation is linked to obesity. Somatostatin (SST) and its analogs have been used to treat pediatric hypothalamic obesity. However, the application of such drugs for the treatment of NAFLD has not been evaluated. OBJECTIVE: This study aimed to investigate the expression levels of important regulators of hepatic lipid metabolism and the possible effect of the SST analog octreotide on these regulators. METHODS: SD rats were assigned to a control group and a high-fat diet group. Obese rats from the high-fat diet group were further divided into the obese and octreotide-treated groups. The body weight, plasma SST, fasting plasma glucose (FPG), insulin, triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C) and free fatty acid (FFA) levels were measured. Hepatic steatosis was evaluated based on the liver TG content, HE staining and oil red O staining. The SREBP-1c, ACC1, FAS, MTP, apoB and ADRP expression levels in the liver were also determined by RT-PCR, qRT-PCR, western blot or ELISA. RESULTS: The obese rats induced by high-fat diet expressed more SREBP-1c, FAS and ADRP but less MTP protein in the liver than those of control rats, whereas octreotide intervention reversed these changes and increased the level of apoB protein. Compared to the control group, obese rats showed increased liver ACC1, SREBP-1c and apoB mRNA levels, whereas octreotide-treated rats showed decreased mRNA levels of apoB and SREBP-1c. This was accompanied by increased body weight, liver TG contents, FPG, TG, TC, LDL-C, FFA, insulin and derived homeostatic model assessment (HOMA) values. Octreotide intervention significantly decreased these parameters. Compared to the control group, the obese group showed a decreasing trend on plasma SST levels, which were significantly increased by the octreotide intervention. CONCLUSION: Octreotide can ameliorate hepatic steatosis in obese rats, possibly by decreasing hepatic lipogenesis and increasing TG export from hepatocytes.